Some Results on Coincidence Points for Contractions in Intuitionistic Fuzzy n-Normed Linear Space: Nabanita Konwar, Pradip Debnath - Team, Support (Thai Journal of Mathematics, 2019)
In this paper, we prove some new coupled coincidence point theorems for two types of contraction mappings - one having commutative condition and other having non-commutative condition in an intuitionistic fuzzy n-Banach space. Our results extend and generalize some important existing classical coupled coincidence point theorems in literature. Some newly constructed examples support the non-triviality of our results.